Star trek, the next generation motion picture collection [videorecording (Blu-Ray)] - Berman, Rick; Moore, Ronald D.; Braga, Brannon; Piller, Michael, 1948-2005; Carson, David, 1948-; Logan, John, 1961-; Baird, Stuart; Frakes, Jonathan; Stewart, Patrick, 1940-; Spiner, Brent; Burton, LeVar; Dorn, Michael, 1952-; et al. (Paramount, 2016)
Includes all 4 movies featuring Captain Picard and crew.